Factors Associated With Participation in Clinical Trials Among Patients With Lupus. Issue 3 (24th April 2022) - Harry, Onengiya; Langefeld, Carl D.; Crosby, Lori E.; Modi, Avani C.
Abstract : Background/Objective: Participation rates for clinical trials, including lupus trials, in the United States are low, but are even lower for underrepresented minorities. The impact of underrepresentation in trials can be far-reaching and is problematic because female subjects of color with lupus experience greater morbidity and mortality. As such, the overarching goal of this study was to characterize the factors that influence participation in lupus clinical trials. Methods: The Lupus and Allied Diseases Association, the Lupus Foundation of America, and the Lupus Research Alliance collected data for their externally led Patient-Focused Drug Development Initiative—for the purpose of understanding and improving the rates of participation in lupus-related clinical trials. Participants completed a 46-question survey (in English or Spanish) electronically or on paper, which was distributed online or at lupus events. Logistic regression was used to test whether demographic and disease characteristics were associated with participation in past lupus trials. Results: Data were available for 2220 respondents. Black respondents with lupus were more likely, than their White and Hispanic counterparts, to have participated in past clinical trials ( p < 0.05). Although not statistically significant, Hispanic respondents were also more likely to have participated than their White counterparts (odds ratio, 1.40; 95% confidence interval, 0.96–2.11). Both demographic (ie, race/ethnicity) and medical (ie, disease severity defined as more organ involvement) factors seem to be important determinants of participation in clinical trials ( p < 0.05). Conclusions: Combining the results from this study and prior research provides insight into recruitment strategies to increase participation rates of historically underrepresented minorities.